Sustainable management of soils in production units (Agroindustria, Sociedad y Ambiente, 2020)
The research presented here is produced from the essay modality, a topic that the author considers a priority to associate with the Plan de la Patria 2019-2025 from a comprehensive and emergent vision of reality, in National Objective 5, from the understanding of the forms of production of natural resources from the sustainable management of soils for the Production Units, specifically in the Production Units (UP's) of the Biruaca Achaguas Axis (EBA), of the Apure State, linking the theoretical and legal framework , the relations of interdependence and evaluation of the evaluation of the Agro-Ecological proposals, from the theoretical network of the General Theory of Systems of Bertalanlffy, Ecological Bronfenbrenner, of the Endogenous Development of Sunkel, of Location of the Thunen Agricultural Activity and legal tools in force, through the post-positivist perspective, with a phenomenological approach by Martínez and Dilthey's hermeneutics exposed by Martínez to understand how human action should theoretically develop in the UP's, whose findings detect that the UP's apply integrated soil management in a traditional way, with an orientation to ecosystem protection, interpretation of Sustainability, radiates a pattern of family consumption, but not extensive, contributing to internal, non-local sustainability, and in the Interdependence and Assessment of Agroecological Proposals, they are sustained from primary production to distribution and production, through sustainable productive policies and resilient.
Keywords: Integrated Soil Management; Sustainability, Production Units; Interdependence and Assessment of Agroecological Proposals